Insight into effects of polyethylene microplastics in anaerobic digestion systems of waste activated sludge: Interactions of digestion performance, microbial communities and antibiotic resistance genes. (1st October 2022) - Shi, Jianhong; Dang, Qiuling; Zhang, Chuanyan; Zhao, Xinyu
Abstract: The environmental risks of microplastics (MPs) have raised an increasing concern. However, the effects of MPs in anaerobic digestion (AD) systems of waste activated sludge (WAS), especially on the fate of antibiotic resistance genes (ARGs), have not been clearly understood. Herein, the variation and interaction of digestion performance, microbial communities and ARGs during AD process of WAS in the presence of polyethylene (PE) MPs with two sizes, PE MPs-180μm and PE MPs-1mm, were investigated. The results showed that the presence of PE MPs, especially PE MPs-1mm, led to the increased hydrolysis of soluble polysaccharides and proteins and the accumulation of volatile fatty acids. The methane production decreased by 6.1% and 13.8% in the presence of PE MPs-180μm and PE MPs-1mm, respectively. Together with this process, hydrolytic bacteria and acidogens were enriched, and methanogens participating in acetoclastic methanogenesis were reduced. Meanwhile, ARGs were enriched obviously by the presence of PE MPs, the abundances of which in PE MPs-180μm and PE MPs-1mm groups were 1.2–3.0 times and 1.5–4.0 times higher than that in the control by the end of AD. That was associated with different co-occurrence patterns between ARGs and bacterial taxa and the enrichment of ARG-hosting bacteria caused by the presence of PE MPs. Together these results suggested the adverse effects of PE MPs on performance and ARGs removal during AD process of WAS through inducing the changes of microbial populations. Graphical abstract: Image 1 Highlights: The effects of PE MPs with two sizes in AD systems of WAS were investigated. PE MPs promoted hydrolysis and acidification and inhibited methanation processes. Microbial communities associated with AD performance were changed by PE MPs. ARGs were enriched by PE MPs during AD process. PE MPs resulted in different ARG-taxa associations and the enrichment of ARG-hosts.